Close Stellar Encounters: Investigating the Distribution of Minimum Distances of Sun-Star and Star-Star Approaches - Pedersen,Anton (Bachelor's Thesis in Mathematical Sciences, 2025)
Close stellar encounters play a critical role in shaping planetary systems by perturbing the orbits of minor body populations like the Oort Cloud and the orbits of planets. Using data from the Gaia DR3 catalogue, this work quantifies close stellar encounters, investigating both Sun-star and star-star interactions. Assuming that stars move in straight lines, encounter distances and times were computed. A sampling method was used to derive confidence intervals for the encounter parameters. In the case of solar encounters, an analytical expression for the encounter distance distribution was derived and used to estimate encounter rates. The results indicate that approximately 2% of Sun-like stars experience an encounter within 100 AU over 4.6 Gyr. After filtering out bound systems, 193 star pairs with median encounter distances of less than 0.05 pc were identified. For solar encounters, six stars were found to approach within 0.5 pc. The closest being Gliese 710 with a median encounter distance of 0.051 pc. This study enhances our understanding of the local dynamical environment and establishes a framework for identifying significant close encounters.
Keywords: Stellar encounters; Close stellar approaches; Gaia DR3; Encounter rate; Isotropic velocities; Minimum separation distribution; Binary star filtering; Linear motion approximation